Do we really need a multilateral investment agreement? - Axel Berger (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
We currently observe a renaissance of the debate about a multilateral investment agreement (MIA). The last attempts to establish such an agreement failed in 1998 at the Organisation for Economic Co-operation and Development (OECD) and in 2003, as part of the Doha Development Agenda of the World Trade Organization (WTO). The reasons for these failures are both the resistance of emerging countries and developing countries to one-sided policies mainly aimed at protecting international investors, and divergences among industrialised countries, particularly regarding the liberalization of market access regulations. The proponents name several arguments in favour of a resumption of negotiations about an MIA: First, we can now observe a fundamental shift in global investment flows. Companies from emerging countries are increasingly investing abroad and aim at a better protection of their foreign direct investment (FDI) in developing and industrialised countries. The traditional criticism put forward by influential, emerging countries against an MIA appears to be weakening as the result of a growing convergence of interests. Secondly, among industrialised countries themselves there is a growing consensus regarding international investment rules. One sign of this are the Shared Principles for Inter national Investment , adopted in 2012 by the EU and the U.S.A., whose purpose is to smooth the way for a Transatlantic Trade and Investment Partnership . With this gradual convergence, in particular regarding the inclusion of market access provisions, a further stumbling block along the way to an MIA appears to have been done away with. Thirdly, the increasing regionalisation of investment rulemaking is advanced as an argument which can facilitate the leap to the next-higher, multilateral level. As a result of socalled Mega-Regionals - like the Transpacific Partnership between the U.S.A. and 10 other countries in the Pacific Region, the Regional Comprehensive Economic Partnership between the Association of Southeast Asian Nations (ASEAN) and six other countries, including China or the planned Transatlantic Trade and Investment Partnership - it is possible that a consolidation of investment rules will arise which would simplify the negotiations about an MIA. These current trends can in fact help to smooth the path to a global accord. However, the main question driving the international debate should not be whether it is possible to establish an MIA. What is more important is the question whether the institutional form of an MIA is suitable for effectively solving the most pressing challenges in the current investment regime. This is not very likely, since an MIA is unlikely to lead to significantly more FDI flows or to give stronger consideration to the interests of the developing countries. An MIA will most likely also not lead to greater coherency between the investment rules and other policy areas. It is more promising to tackle these challenges in the context of regional co-operation, since this permits better accommodation of the treaty contents to the specific needs of the countries involved. Negotiations at the regional level should be supplemented by co-ordination efforts on the global level. The G-20 is the appropriate orchestrator for talks about these systemic questions, talks which in turn should be carried on with the inclusion of the OECD, WTO, and the United Nations Conference for Trade and Development (UNCTAD) and other stakeholders.
Keywords: 330; Handel und Investitionen; Regionale + globale + transnationale Governance